Colonoscopy - Kaminski, Michal F.; Zagorowicz, Edyta (Endoscopy, 2014)
Several high-quality studies pertinent to colonoscopy were presented at Digestive Disease Week (DDW) 2014. The following review discusses studies that are considered to address some of the most burning questions in colonoscopy research: quality of colonoscopy and its measurement, surveillance intervals for adenomas, the treatment of diminutive adenomas, basic and advanced polypectomy techniques, and microbiome changes in relation to colonoscopy.